Efficacy of proximal femoral nail augmentation in unstable intertrochanteric fracture - J., Purushotham V.; Khan, M. Ayyub; Kumar, Navneeth (International Journal of Research in Orthopaedics, 2020)
Background: To assess the short term functional and radiological outcome of unstable intertrochanteric fracture fixation using proximal femoral nail with augmentation using Cannulated Cancellous (CC) screw or Stainless Steel (SS) wiring. Methods: A prospective study was conducted with 20 cases of unstable intertrochanteric femoral fractures from May 2017 to March 2019. Six females and fourteen male patients in the age group between 40 and 80 years were included in this study. There were 8 cases of AO31A2 and 12 cases of AO31 A3. Fracture were fixed by proximal femoral nail with augmentation by an additional CC screw or encirclage with SS wires to strengthen the lateral trochanteric wall. Results: Fracture union was achieved in all cases with a mean period of 15.4 weeks. Patients were followed up for a period of 6 months. At the end of follow up the Modified Harris Hip Score was found to be more than 90 % in 16 cases. Conclusion: Augmentation of proximal femoral nail in unstable intertrochanteric fracture with additional screw or cerclage wire increases the efficacy and stability of construct, aiding union and expedition of time to union.